P89 Novel mechanisms of immunomodulation by vitamin D and α-1-antitrypsin. (14th November 2013) - Rice, LV; Dimeloe, S; Raynes, J; Gupta, A; Pfeffe, O; Richards, D; Urry, Z; Farooque, S; Ozegbe, P; Hornsby, E; Nyon, M; Haq, I; et al.
Abstract : Vitamin D deficiency/insufficiency has been associated with poor respiratory health and a predisposition to respiratory disease. Local activation of vitamin D in the airways is important for antimicrobial defenses and suppression of inflammatory responses via the generation of a tolerogenic immune environment. One of the most highly unregulated proteins by vitamin D in CD4+ T-cells is the serine protease inhibitor α-1-antitrypsin. In addition to controlling the pro-inflammatory effects of neutrophil elastase, α-1-antitrypsin also acts via other pathways as an immunomodulator. We have identified a novel axis of immune modulation by vitamin D; where α-1-antitrypsin is able to induce IL-10 production in PBMCs via an interaction with the complement component C3a. Our in vitro findings are supported by in vivo correlations of serum vitamin D, α-1-antitrypsin, C3a and IL-10 in the airways of both asthmatics and healthy controls from a paediatric cohort. We propose that vitamin D is an upstream regulator of the α-1-antitrypsin/C3a/IL-10 axis, providing attractive therapeutic options to promote tolerance in a range of inflammatory diseases.